Effect of IV glyburide on adjudicated edema endpoints in the GAMES-RP Trial. (4th December 2018) - Kimberly, W. Taylor; Bevers, Matthew B.; von Kummer, Rüdiger; Demchuk, Andrew M.; Romero, Javier M.; Elm, Jordan J.; Hinson, Holly E.; Molyneaux, Bradley J.; Simard, J. Marc; Sheth, Kevin N.
Abstract : Objective: In this secondary analysis of the Glyburide Advantage in Malignant Edema and Stroke (GAMES-RP) Trial, we report the effect of IV glyburide on adjudicated, edema-related endpoints. Methods: Blinded adjudicators assigned designations for hemorrhagic transformation, neurologic deterioration, malignant edema, and edema-related death to patients from the GAMES-RP phase II randomized controlled trial of IV glyburide for large hemispheric infarct. Rates of these endpoints were compared between treatment arms in the per-protocol sample. In those participants with malignant edema, the effects of treatment on additional markers of edema and clinical deterioration were examined. Results: In the per-protocol sample, 41 patients received glyburide and 36 received placebo. There was no difference in the frequency of hemorrhagic transformation (n = 24 [58.5%] in IV glyburide vs n = 23 [63.9%] in placebo, p = 0.91) or the incidence of malignant edema (n = 19 [46%] in IV glyburide vs n = 17 [47%] in placebo, p = 0.94). However, treatment with IV glyburide was associated with a reduced proportion of deaths attributed to cerebral edema (n = 1 [2.4%] with IV glyburide vs n = 8 [22.2%] with placebo, p = 0.01). In the subset of patients with malignant edema, those treated with IV glyburide had less midline shift ( p < 0.01) and reduced MMP-9 (matrix metalloproteinase 9) levels ( p < 0.01). The glyburide treatment group had lower rate of NIH Stroke Scale (NIHSS) increase of ≥4 during the infusion period (n = 7 [37%] in IV glyburide vs n = 12 [71%] in placebo, p = 0.043), and of change in level of alertness (NIHSS subscore 1a; n = 11 [58%] vs n = 15 [94%], p = 0.016). Conclusion: IV glyburide was associated with improvements in midline shift, level of alertness, and NIHSS, and there were fewer deaths attributed to edema. Additional studies of IV glyburide in large hemispheric infarction are warranted to corroborate these findings. ClinicalTrials.gov identifier: NCT01794182. Level of evidence: This study provides Class II evidence that for patients with large hemispheric infarction, IV glyburide improves some edema-related endpoints.